2019
DOI: 10.33320/maced.pharm.bull.2018.64.02.003
|View full text |Cite
|
Sign up to set email alerts
|

A comparative in vitro dissolution study of generic moxifloxacin immediate-release film coated tablets and referent pharmaceutical product

Abstract: Dissolution testing of generic immediate release solid dosage forms represents a valuable tool to obtain dissolution profiles and to establish the similarity/dissimilarity between tested dosage forms. In this study, the in vitro dissolution profiles of generic immediate-release moxifloxacin (MOX) film coated tablets and a referent pharmaceutical product were compared and evaluated. The dissolution behavior of the generic product was investigated in three different dissolution media (pH=1.2, 4.5 and 6.8). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…A study carried out in Pakistan in 2019 evaluated four different brands of multi-source moxifloxacin tablets (400 mg), finding f2 values of 77.20, 69.56, 76.98, and 82.17 respectively, which indicated that there was similarity in the release profile of the four brands compared to the reference brand (10). An investigation carried out in Macedonia in 2018, evaluated a generic drug of moxifloxacin tablets (400 mg), determining the f2 value of 50.85 at pH 1.2, concluding that the similarity of dissolution in vitro could be used as an important part of the approach to ensure bioequivalence in vivo and therapeutic equivalence (11).…”
Section: Introductionmentioning
confidence: 99%
“…A study carried out in Pakistan in 2019 evaluated four different brands of multi-source moxifloxacin tablets (400 mg), finding f2 values of 77.20, 69.56, 76.98, and 82.17 respectively, which indicated that there was similarity in the release profile of the four brands compared to the reference brand (10). An investigation carried out in Macedonia in 2018, evaluated a generic drug of moxifloxacin tablets (400 mg), determining the f2 value of 50.85 at pH 1.2, concluding that the similarity of dissolution in vitro could be used as an important part of the approach to ensure bioequivalence in vivo and therapeutic equivalence (11).…”
Section: Introductionmentioning
confidence: 99%